Subtype-specific atypical B cell profiles in myasthenia gravis reveal distinct immunopathological pathways - Sikorski, Patricia M.; Kaminski, Henry J.; Vincent, Angela; Bauman, Taylor; Jacobson, Leslie; Kusner, Linda L. (Frontiers in Immunology, 2025)
IntroductionAtypical B cell (atBC) subsets display significant heterogeneity across autoimmune diseases, complicating efforts to define their role and therapeutic potential. We hypothesized that this heterogeneity reflects the responses to specific immunopathology, resulting in disease-specific profiles. The myasthenia gravis (MG) subtypes acetylcholine receptor (AChR)-positive MG and muscle-specific kinase (MuSK)-positive MG provide an ideal model to explore atBCs due to the distinct immune mechanisms driven by IgG1-3 and IgG4 autoantibodies, respectively in the disease.MethodsCD11c+ and IgD−CD27− double-negative (DN) B cells were analyzed by spectral flow cytometry in non-autoimmune controls, AChR-MG, and MuSK-MG. Results were correlated with clinical parameters and antibody levels. In MG subtypes, atBC subsets were further examined for the impact of disease onset and prior rituximab treatment. CD11c+ B cells were stimulated in vitro to assess antibody secreting cell (ASC) differentiation.ResultsCD11c+ and DN2 B cells were increased in late-onset AChR-MG, while MuSK-MG featured expanded DN3 B cells linked to disease severity. CD20 expression in atBCs was differentially expressed between MG subtypes, with higher levels in late-onset AChR-MG and significantly reduced levels in MuSK-MG. CD11c+ B cells were reduced after anti-CD20 treatment in MuSK-MG, whereas DN B cells were unaffected. Functionally, CD11c+ B cells from MuSK-MG exhibited greater ASC differentiation and autoantibody production.DiscussionMG subtypes exhibit distinct atBC profiles linked to immunopathology and disease onset. These findings reveal subtype-specific pathways that regulate atBCs and highlight their potential as therapeutic targets in both IgG1-3- and IgG4-mediated autoimmunity.